Teledetection de l'evolution des ressources fourrageres par satellite: Progres dans l'etalonnage d'un indice radiometrique et premieres applications au Gourma (Sahel malien) - Hiernaux, Pierre H.Y. (1988)
Evaluates relationship between NDVI (nomalized difference vegetation index) and above-ground biomass, between maximum NDVI and end-of-growing season biomass; and between the integral of the NDVI curve or NDVI increments overtime and actual biomass. Describes atmospheric interference and technical problems affecting the special vegetation index.